Analysis of Stock Valuation Using Price Earning Ratio, Price to Book Value, and Discount Cash Flow Methods in LQ45 Companies for the Period 2022-2024 - Annisa Epriliana Putri; Ikhwan HS; Budiman (Majapahit Journal of Islamic Finance and Management, 2026)
Capital markets play a crucial role in the economy, making it essential for investors to apply accurate valuation methods in investment decision-making. This study aimed to determine the fair value of stocks of companies listed in the LQ45 index using the Price Earnings Ratio (PER), Price to Book Value (PBV), and Discounted Cash Flow (DCF) methods during the 2022–2024 period, and to examine the differences among the three valuation results. A quantitative approach was employed using secondary data obtained from the Indonesia Stock Exchange (www.idx.co.id) and the annual reports of each respective company. The analytical procedures included calculating stock fair values using the PER, PBV, and DCF methods, followed by a comparative analysis. The Kruskal-Wallis test was subsequently applied to assess statistically significant differences across methods. The results indicated that the Asymptotic Significance (Asymp. Sig.) value was 0.000 < 0.05, confirming statistically significant differences among the fair values generated by the PER, PBV, and DCF methods. These differences were attributed to the distinct analytical approaches and underlying assumptions associated with each valuation method.